STRATEGI IMPLEMENTASI KEBIJAKAN PENANGGULANGAN KEMISKINAN DI KOTA TASIKMALAYA - Iwan Satibi; Undang Sudrajat (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the strategy of poverty reduction policies in the City of Tasikmalaya by using a benchmarking model. This study uses the mix methods, which combine qualitative and quantitative approaches. The results of the study found that the implementation of poverty reduction policies in the City of Tasikmalaya, had not yet been fully effective. Therefore, a strategy is needed to streamline the implementation of poverty reduction policies that refer to the results of benchmarking. The results cover two main things, namely the need for the pollitical will of the regional head and the establishment of a special institution that handles poverty.